2004
DOI: 10.2165/00023210-200418050-00002
|View full text |Cite
|
Sign up to set email alerts
|

Management of Insomnia in Patients with Chronic Pain Conditions

Abstract: The management of insomnia in patients experiencing chronic pain requires careful evaluation, good diagnostic skills, familiarity with cognitive-behavioural interventions and a sound knowledge of pharmacological treatments. Sleep disorders are characterised by a circular interrelationship with chronic pain such that pain leads to sleep disorders and sleep disorders increase the perception of pain. Sleep disorders in individuals with chronic pain remain under-reported, under-diagnosed and under-treated, which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 82 publications
1
42
0
4
Order By: Relevance
“…In other words, the level of pain at baseline resulted in worsening problems in getting to sleep even when the level of pain did not intensify over time. This is consistent with previous research has shown that problems with disturbed sleep can become chronic once they have begun, even if the original trigger is no longer present (Stiefel & Stagno, 2004). Adequate treatment for pain may prevent both current and future sleep problems for women with metastatic breast cancer.…”
Section: Painsupporting
confidence: 91%
See 1 more Smart Citation
“…In other words, the level of pain at baseline resulted in worsening problems in getting to sleep even when the level of pain did not intensify over time. This is consistent with previous research has shown that problems with disturbed sleep can become chronic once they have begun, even if the original trigger is no longer present (Stiefel & Stagno, 2004). Adequate treatment for pain may prevent both current and future sleep problems for women with metastatic breast cancer.…”
Section: Painsupporting
confidence: 91%
“…Previous research has shown that pain and disturbed sleep can have a circular pattern in relation to each other, with pain triggering disturbed sleep and disturbed sleep increasing perceptions of pain (Latham & Davis, 1994;Stiefel & Stagno, 2004). Women with metastatic breast cancer and high levels of pain may be at risk for problems getting to sleep and staying asleep and those with these types of disturbed sleep may be at risk for even greater pain.…”
Section: Painmentioning
confidence: 99%
“…low physical activity [15,23,24], alcohol intake [25,26], smoking [27][28][29][30][31]), poor physical health [32,33] and physical symptoms (e.g. pain [23,[34][35][36][37], vasomotor symptoms [38][39][40][41][42][43]), and poor psychosocial functioning (e.g. poor social functioning [44,45], life stress [15,[46][47][48][49], depression/depressive symptoms [19,23,50], and personality traits such as anger/hostility [51]).…”
Section: Introductionmentioning
confidence: 99%
“…Insbesondere Erkrankungen, die mit einer Schmerzsymptomatik verbunden sind, wie z.B Arthritiden, Neuropathien, aber auch Schmerzen bei Patienten mit Neoplasmen gehen mit Schlafstörungen einher [25][26][27]. Es ist dabei die wechselseitige Verstärkung der Schlafstörung und der Schmerzsymptomatik zu beachten, die ein Aufbrechen eines sich selbst intensivierenden Circulus vitiosus notwendig macht [26,28].…”
Section: Medizinische Neurologische Und Psychiatrische Erkrankungenunclassified
“…Es ist dabei die wechselseitige Verstärkung der Schlafstörung und der Schmerzsymptomatik zu beachten, die ein Aufbrechen eines sich selbst intensivierenden Circulus vitiosus notwendig macht [26,28].…”
Section: Medizinische Neurologische Und Psychiatrische Erkrankungenunclassified